Isolation of fungi potentially producing enzymes of agroindustrial interest: A qualitative analysis of the standardization of the LED light Method - Silva, Jean Cristhian da; Carmo, Gabriel Freitas Borghetti do; Antunes, Nicole Maria Santos; Bragança, Caio Roberto Soares; D’Ávila, Vinícius de Abreu (Acta Scientiarum. Biological Sciences, 2025)
The biotechnology industry plays a crucial role in the advancement of agronomy, contributing increasingly to each stage of its development. Microbial bioprospecting is a highly diverse field with significant agroindustrial potential, as nature provides a vast range of microorganisms suitable for such applications — including lipase-producing strains. As part of an initiative to establish a fungal collection at the Universidade do Estado de Minas Gerais (UEMG) – Passos Unit, 22 fungal isolates were obtained from various natural sources, 17 of which demonstrated lipase production. Fungal isolates with the highest lipolytic activity were derived from wet soil in calf paddocks, oral residues from calves post-nursing, and treated sewage sludge. This study introduces a standardized method using LED light for detecting lipolytic activity — a technique that to the best of our knowledge has not previously been applied to microorganisms. LED light presents a safer alternative to UV light, which can compromise sample integrity and pose health risks to users. This novel approach highlights the diversity of lipase-producing fungi from distinct environmental sources. The study aims to evaluate and qualitatively assess fungal enzymatic activity through this innovative methodology, facilitating the selection of strains with high enzymatic potential for agroindustrial applications.